Satisfaction in retirement: a comparison between Brazil and Portugal - Amorim, Silvia M. (2020)
Purpose: The objective of this study was to verify the difference in levels of satisfaction among retirees residing in Brazil and Portugal. Originality/value: The world aging process creates challenges in the sense of providing well-being for those who have decided to retire, considering the importance of this moment in people’s lives. Despite this, there are many gaps in studies on well-being in retirement, especially cross-cultural studies. Design/methodology/approach: This is a cross-sectional, quantitative study involving 1,441 retirees, 997 Brazilians and 444 Portuguese, who responded to the Retirement Satisfaction Inventory (RSI) and sociodemographic issues. For the analyses of the data, we performed multigroup confirmatory factor analyses, internal consistency and validity analyses, invariance verification and comparison of latent means of the instrument factors between the two countries. Findings: The results pointed to a consistent instrument structure for the two countries, which made it possible to compare them. There were no significant differences between countries in the factors related to satisfaction with individual resources and social relationships. However, in the third factor of the instrument – satisfaction with collective resources – the participants in Portugal presented a mean significantly higher than the Brazilian participants. At the end, the conclusion of the measure of satisfaction in retirement is concluded, and the differences in public service offerings between Brazil and Portugal are discussed, pointing to the specific needs of the retired population.